2017
DOI: 10.33591/sfp.43.3.u1
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Caring for Patients with Complex Comorbidities for Family Physician: The SBAR4 model

Abstract: Providing comprehensive and continuing care to patients is the forte of family physicians. The burden of providing such care to patients with complicated co-morbidities is increasing rapidly in ageing populations. Primary care systems around the world are ill equipped to face such a challenge. Family physicians need to hone their skills in this area of care. In this article, we introduce the SBAR4 model and propose it as a framework for managing patients with complex co-morbidities. This model is easy to learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Previous studies found that open awareness as a medical and ethical mandate was valued in Western countries and showed that patient autonomy was not fully implemented in Eastern cultures 21,37 . Although the gatekeeper role of the family in Eastern countries was confirmed, family members from Western and Eastern countries were both cautious about revealing the truth, especially negative information (risks, compliance, survivorship, and death), although patients preferred to be informed about details of their own cancer 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that open awareness as a medical and ethical mandate was valued in Western countries and showed that patient autonomy was not fully implemented in Eastern cultures 21,37 . Although the gatekeeper role of the family in Eastern countries was confirmed, family members from Western and Eastern countries were both cautious about revealing the truth, especially negative information (risks, compliance, survivorship, and death), although patients preferred to be informed about details of their own cancer 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The awareness context was culturally relevant. Although open awareness was found to be conducive to pain management, psychological well-being, and quality of life, the patient’s autonomy remained challenged because of the emphasis on family determination in many Eastern countries (Iran, Japan, Singapore, and Saudi Arabia) 19–23 . In China, family members tended to be intimately involved in the decision-making process, diagnostic disclosure, and doctor-patient communication 14,24 .…”
mentioning
confidence: 99%
“…Cultural differences in attitudes towards truth-telling exist; however, these differences should not be used as excuses not to respect individual rights and preferences of cancer patients by making assumptions based on their age, sex, type of cancer, language and/or cultural background [18]. It has been found that physicians from Japan agree upon the concealment of the truth [19] and similar attitudes of patient nondisclosure have been observed in Singapore [20].…”
Section: The Ethical Dilemma Of Communicating Cancer Diagnosismentioning
confidence: 98%
“…11 ere is also a trend towards delivering this care through forming inter-professional teams or multi-disciplinary teams which has been shown to improve outcomes. 8 e SBAR4 framework, proposed by Lee et al 12 in an earlier publication on complex care combines the elements of the SBAR model of inter-disciplinary communication as well as the tasks of consultations described by Pendleton.…”
Section: Introductionmentioning
confidence: 99%